Seismic reliability of legged wine storage tanks retrofitted by means of a seismic isolation device. (1st March 2017) - Colombo, J.I.; Almazán, J.L.
Highlights: The seismic reliability of two typical legged wine storage tanks is investigated. Probability of occurrence of the limit state is reduced through seismic isolation. A novel seismic isolation system is proposed for legged wine storage tanks. Abstract: Due to the booming of the winery industry in some seismic countries such as, the U.S, Italy, New Zealand, Chile and Argentina, the seismic protection of wine storage tanks may be of a practical importance. Wine storage tanks are classified in two major groups: continuously supported tanks and legged tanks. Previous research has described the seismic reliability of continuously-supported tanks, with and without seismic protection devices. Conversely, the seismic reliability of legged wine tanks has not been reported. Therefore, in this study, the seismic reliabilities of two typical stainless steel legged wine storage tanks (one of 3000 L capacity and one of 17, 100 L capacity), used for fermentation and wine storage, in original and updated states are assessed by means of simulation. For the updated state, a non-linear isolation system for seismic isolation of legged wine tanks is used. The effect of the isolation system was numerically estimated by performing a group of non-linear time history analyses for each tank. Each non-linear time history analysis was obtained by means of a mathematical model. A set of different seismic ground motions was used for the purpose of obtaining robust results in the reliability analysis. Finally, the seismic reliability analysis shows that, for steel legged wine storage tanks, the effect of the isolation system would reduce the limit state probability in the order of 90%.